The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1037/0735-7028.30.5.447
|View full text |Cite
|
Sign up to set email alerts
|

Scientizing and routinizing the assessment of suicidality in outpatient practice.

Abstract: Suicidal patients are difficult and challenging clinical problems. Conceptual tools aid the clinician in organizing and evaluating the clinical situation. The authors provide a framework for suicide risk assessment that emphasizes 2 domains-history of past attempt and the nature of current suicidal symptoms-that have emerged in suicide research as crucial variables. These domains, when combined with other categories of risk factors, produce a categorization of risk for the individual patient, leading, in turn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
282
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 267 publications
(288 citation statements)
references
References 32 publications
4
282
0
2
Order By: Relevance
“…Clarification early in the assessment process helps improve subsequent efforts to monitor risk over time (139). Joiner et al (140) offered a general framework for suicide risk evaluation that included seven domains: 1) previous suicidal behavior, 2) the nature of current suicidal thinking behaviors, 3) precipitant stressors, 4) general psychiatric symptoms 5) the presence of hopelessness, 6) impulsivity and self-control 7) protective factors. A standard approach that explore all these domains is recommended.…”
Section: Suicide Risk Evaluationmentioning
confidence: 99%
“…Clarification early in the assessment process helps improve subsequent efforts to monitor risk over time (139). Joiner et al (140) offered a general framework for suicide risk evaluation that included seven domains: 1) previous suicidal behavior, 2) the nature of current suicidal thinking behaviors, 3) precipitant stressors, 4) general psychiatric symptoms 5) the presence of hopelessness, 6) impulsivity and self-control 7) protective factors. A standard approach that explore all these domains is recommended.…”
Section: Suicide Risk Evaluationmentioning
confidence: 99%
“…Section B). Den er laget slik at vi kan vurdere det vi ut fra nyere empirisk forskning mener er de farligste risikovariablene (Joiner, Walker, Rudd & Jobes, 1999;Oordt et al, 2003).…”
Section: Steg 2 -Samarbeid Om Vurderingen Ved Hjelp Av Sff (Suicide Sunclassified
“…With regard to risk assessment, it is not enough to simply ask a client about the presence of suicidal ideation (Gross, 2005;Joiner et al, 1999;Simon, 2002); other factors must be considered as well and included in the clinician's risk assessment. For example, Beck has shown that future acts of violence are better predicted by an individual's previous behavioral pattern than by verbal threats of violence (1998).…”
Section: The Role Of Impulsivity In the Foreseeability Of Suicidementioning
confidence: 99%